(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Non-linear loads like direct current loads and induction motor drives are a major source of harmonics in the power system. Multipulse converters are widely used to overcome the problem of harmonics. This thesis highlights the performance comparison of different multipulse converters which are simulated in MATLAB/SIMULINK. Performance comparison of the 6-pulse, 12-pulse, 24-pulse and 48-pulse converters feeding RL-load is performed. The phase shift in the converters is achieved by using ziz-zag phase shifting transformers. The Total Harmonic Distortion (THD) in input current and input voltage along with ripple content in the output voltage and output current are measured and their corresponding waveforms are observed. Also, performance comparison of 6-pulse, 12-pulse, 24-pulse and 48-pulse converters is performed. The results obtained with a multipulse converter are compared with those obtained with the six pulse converter. It is observed that multipulse converters provide better results in terms of THD in input voltage and input current. It is found that as the pulse number of a converter increases, THD in input voltage and input current along with ripple content in the output voltage and output current is decreased.